Improving Student Motivation and Learning Outcomes Through the Application of Problem-Based Learning Models in Mathematics Learning Specialization - Simson, Simson (Pinisi Journal of Education and Management, 2023)
Teachers as educational professionals have an important role in the teaching and learning process. Teachers must be able to explain their knowledge to their students through managing learning by applying teaching approaches and models that are appropriate to the subject matter and cognitive level of students. aims to improve the mathematics learning abilities of XI IPA 2 students at SMAN 7 Sigi even semester for the 2022/2023 academic year in the basic competence "Analyzing division and factorization of polynomials" using Problem-Based Learning. This study used classroom action research with a sample of 37 people consisting of 9 men and 28 women with data collection techniques, namely 1) non-test techniques consisting of observation and documentation, and 2) test techniques. Data validity was carried out through source triangulation and method triangulation with data analysis techniques. The data analysis techniques used in this study are non-test techniques and learning achievement tests. The results of this study indicate that 1) the application of the Problem-Based Learning (PBL) learning model that is used as a model in this learning is in fact capable of increasing residual learning motivation in mathematics learning specialization class XI IPA 2 SMAN 7 Sigi even semester of the 2022/2023 academic year; 2) The application of the Problem-Based Learning (PBL) learning model that is used as a model in this learning is in fact able to improve the remaining learning outcomes in mathematics learning specialization for class XI IPA 2 SMAN 7 Sigi even semester of the 2022/2023 academic year; 3) The application of the Problem-Based Learning (PBL) learning model that is used as a model in this learning is in fact able to increase motivation and residual learning outcomes in mathematics learning specialization class XI IPA 2 SMAN 7 Sigi even semester of the 2022/2023 academic year